Stress and Sleep Quality among the Elderly During The COVID-19 Pandemic: A cross-sectional study - Bella Bella; Santa Maria Pangaribuan; Sri Hunun Widiastuti (Universitas Muhammadiyah Surakarta, 2023)
Elderly is someone who has reached the age of 60 years and over. Stress experienced by the elderly affects life and has an impact on various problems such as difficulty sleeping, discomfort, irritability, and difficulty concentrating. The quality of sleep in the elderly has several aspects such as sleep duration, sleep literacy, and subjective aspects of sleep. In the government program during the Covid-19 pandemic, the Lockdown program was issued, so that the elderly have limited space for movement, are indifferent to others, and fear being exposed to COVID-19. The research objectiveis is determine the relationship between stress and sleep quality in the elderly during the Covid-19 pandemic. This research uses an analytical observational cross-sectional approach. The sample obtained as many as 111 respondents by means of convenience sampling. This study shows the most stress level is moderate stress (45.9%), most respondents' sleep quality level is good sleep quality (94.6%), the subjective sleep quality level is mostly adequate poor (45.0%), the longest respondent's sleep duration is <5 hours (40.5%), the respondent's sleep latency is at most 31-60 minutes (76.6%), the most respondent's sleep efficiency is >85% (67.6% ), the most respondents' sleep disorders were 10-18 (71.2%), the most respondents' sleep dysfunction was 3-4 (57.7%), the respondents had never used sleeping pills in the last month (92.8%), and there was a significant relationship between stress and sleep quality in the elderly during the Covid-19 pandemic with a p-value = 0.001. There is a significant relationship between stress and sleep quality in the elderly during the Covid-19 pandemic, so it is hoped that the puskesmas such as the person in charge of the elderly at the Senen Subdistrict Health Center will carry out activities or socialization to the elderly regarding improving sleep quality and ways to deal with stress.